2018
DOI: 10.1016/j.joule.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and Interface Engineering for Solid-State Sodium Batteries

Abstract: Sodium batteries are considered as promising candidates for large-scale energystorage systems owing to the abundant and low-cost sodium resources. However, many reported sodium batteries are based on conventional organic liquid electrolyte, which would lead to potential safety issues. Developing solid-state electrolyte (SSE) for sodium batteries is an effective way to solve such problems. Nevertheless, how to develop high-performance SSE and compatible interface for constructing solid-state sodium batteries is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
352
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(353 citation statements)
references
References 114 publications
(194 reference statements)
1
352
0
Order By: Relevance
“…In the second system of CPE, the TiO 2 nanoparticles produce more amorphous phase in the polymer matrix and decrease the degree of crystallinity. The increase in amorphicity may increase segmental motion of the polymer chains and improve ionic mobility and ionic conductivity …”
Section: Resultsmentioning
confidence: 99%
“…In the second system of CPE, the TiO 2 nanoparticles produce more amorphous phase in the polymer matrix and decrease the degree of crystallinity. The increase in amorphicity may increase segmental motion of the polymer chains and improve ionic mobility and ionic conductivity …”
Section: Resultsmentioning
confidence: 99%
“…Especially, NASICON shows high water and air stability, wide electrochemical window (>5 V), and unit cation transference number. However, the poor mechanical properties of ceramics cannot properly handle the high interfacial resistances and volume changes in sodium metal batteries . In addition, more and more studies have showed that ceramic electrolytes may not absolutely avoid the dendritic growth issue due to its ignorable defects (cracks, voids, grain boundaries, etc.…”
mentioning
confidence: 99%
“…Especially, anionic group belonging to lithium salt would be absorbed on the surface of nanoparticles, which greatly boosts the dissociation of lithium salt in polymer matrix and releases more Li + . Simultaneously, the surface of nano‐fillers provides some route which is beneficial to Li + transfer . The above‐mentioned advantages can apparently improve the conductivity of PEO.…”
Section: Introductionmentioning
confidence: 99%